Out-of-Pocket Costs for Colposcopy Among Commercially Insured Women From 2006 to 2019. Issue 4 (April 2022) - Fendrick, A. Mark; Dalton, Vanessa K.; Tilea, Anca; Malone, Anita M.; Moniz, Michelle H.
Abstract : (Abstracted from Obstet Gynecol 2022;139:113–115) Colposcopy is an evidence-based, recommended procedure for women with an abnormal initial cervical cancer screening test result. Cervical cancer screening modalities, including Papanicolaou testing and human papillomavirus testing, are covered by the Affordable Care Act without consumer cost sharing for average-risk, age-eligible women.